Firm Competition and Cooperation with Norm-Based Preferences for Sustainability - Roman Inderst; Eftichios S. Sartzetakis; Anastasios Xepapadeas (ZBW - Leibniz Information Centre for Economics, 2022)
We analyze firms incentives to coordinate on the introduction of a more sustainable product variant when consumers preferences for greater sustainability depend on the perceived social norm, which in turn is shaped by average consumption behavior. Such preferences lead to multiple equilibria. If the more sustainable variant allows firms to sufficiently expand their aggregate market share, when a lenient legal regime makes this feasible they will coordinate on the more sustainable outcome. If their aggregate market share however does not expand sufficiently under the more sustainable variant, coordination can forestall a more sustainable outcome. Our analysis thus both confirms and qualifies the notion of a sustainability first-mover disadvantage as a justification for an agreement between competitors, which has gained traction in antitrust. We also provide empirical evidence for norm-based sustainability preferences.
Keywords: 330; Sustainability; Antitrust; Firm Cooperation